Customer Trust Mediates Word of Mouth Impact on Queen Decoration Service Decisions - Nueng, Cinthia Hermiana; Husen, Sjamsier; Mustajab, Duta (Advances: Jurnal Ekonomi & Bisnis, 2024)
Purpose: This study examines the effect of Word of Mouth (WOM) on Customer Trust. To investigate the impact of Customer Trus on the Decision to Use Decoration Services. To examine the impact of Word of Mouth (WOM) on the Decision to Use Decoration Services. Moreover, to explore the impact of Word of Mouth (WOM) on the Decision to Use Decoration Services through Customer Trust. Research Design and Methodology: This study is a quantitative descriptive research study. All customers who had ordered decoration services at Queen Dekorasi, including 140 respondents. Data was collected using field research techniques. The data analysis method used Instrument Tests and Structural Equation Modeling (SEM) Analysis. Findings and Discussion: The results showed that Word Of Mouth positively and significantly affects Customer Trust. Customer Trust has a positive and significant effect on Decisions to Use Services. Word Of Mouth does not significantly affect the decision to use services. Moreover, Customer Trust can mediate the influence of Word of Mouth on the Decision to Use Services. Implications: This research can be considered and evaluated so that service business actors continue paying attention to the word-of-mouth and customer trust factors influencing decisions to use services and increasing public interest in the services offered. Hopefully, this research can add to the knowledge for further research to develop what factors can influence service decisions.